Developing listening skills in teaching English (Eurasian Journal of Learning and Academic Teaching, 2022)
Grammar is not the only language used in language teaching and learning today. Grammar can be taught for a month or two to form a basic concept, but other methods are used. There are different ways of teaching a language, through which we can see how the language is taught today, that is, we can learn from them that the above statements have been confirmed. In the past, grammar was used in language teaching, but now there are different methods. Also, the four-skill English language teaching method is becoming more and more popular today. These are reading, writing, speaking and listening skills. These skills are good at teaching not only English but also other languages. This article provides information on learning and developing listening skills in teaching and learning English.